Copelatus cessaima sp. nov. (Coleoptera: Dytiscidae: Copelatinae): first record of a troglomorphic diving beetle from Brazil - Caetano, Daniel S.; Bená, Daniela De C.; Vanin, Sergio A. (Zootaxa, 2013)
Copelatus cessaima sp. nov. is described from Brazil. The new species was collected in water puddles inside of caves found in an ironstone formation and has typical troglomorphic characters: the eyes and metathoracic wings are absent, the elytra are fused and the body has long setae. This is the second species of Copelatinae reported as troglomorphic and the first record of a troglomorphic Dytiscidae species in Brazil. The modified morphology of the new species and the lack of elytral striae make the placement of C. cessaima sp. nov. in one of the 15 recognized Copelatus species groups difficult. Thus, we assign the new species to a “group unknown” as defined in Nilsson’s world catalogue of the family Dytiscidae.